Polemika między Starowolskim i Przypkowskim. Przyczynek do badań XVII-wiecznego dyskursu wykluczenia i dyskursu tolerancji - Hawrysz, Magdalena (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The paper focuses on two types of the 17th century public discourse – of exclusion and tolerance. The research is based on the analysis of the works of Szymon Starowolski (Braterskie napomnienie, Prawdziwe objaśnienie Braterskiego napomnienia) and Samuel Przypkowski (Braterska deklaracyja) which constitute a polemical chain or a series of works combined on the basis of discussion replies. The purpose of the sketch is to characterize the subjects of the discourse, describe the communication strategies used and reconstruct presented attitudes and values. The subject of the discourse of exclusion assumes the approach of a hegemon attempting to discredit the object of the discourse and lead to its isolation. It invokes to insinuation and emotional arguments. The subject of the discourse of tolerance represents an irenic attitude and presents a society based on amicable coexistence, the will of cooperation, respect for law and freedom of conscience.